2013
DOI: 10.1016/j.neurobiolaging.2013.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β precursor protein as a molecular target for amyloid β–induced neuronal degeneration in Alzheimer's disease

Abstract: A role of amyloid β (Aβ) peptide aggregation and deposition in Alzheimer’s disease (AD) pathogenesis is widely accepted. Significantly, abnormalities induced by aggregated Aβ have been linked to synaptic and neuritic degeneration, consistent with the “dying-back” pattern of degeneration that characterizes neurons affected in AD. However, molecular mechanisms underlying the toxic effect of aggregated Aβ remain elusive. In the last 2 decades, a variety of aggregated Aβ species have been identified and their toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 237 publications
0
34
0
Order By: Relevance
“…It has been reported that the normal physiological function of APP may be compromised by Aβ (Bignante et al, 2013). Direct interactions between Aβ fibrils and APP were described, with Aβ acting to enhance APP multimerization, a potentially toxic mechanism (Lorenzo et al, 2000; Van Nostrand et al, 2002; Lu et al, 2003; Shaked et al, 2006; Sola Vigo et al, 2009; Kedikian et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the normal physiological function of APP may be compromised by Aβ (Bignante et al, 2013). Direct interactions between Aβ fibrils and APP were described, with Aβ acting to enhance APP multimerization, a potentially toxic mechanism (Lorenzo et al, 2000; Van Nostrand et al, 2002; Lu et al, 2003; Shaked et al, 2006; Sola Vigo et al, 2009; Kedikian et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Essential for physiological brain development (neurogenesis and synaptogenesis) and plasticity [26,85]. …”
Section: Pathophysiology Genetics and Functional Brain Processing Umentioning
confidence: 99%
“…Overexpression of APP has been associated with an increase in Aβ42 levels in the brains of foetuses with DS (Teller et al, 1996). Binding of aggregated Aβ to APP is likely to promote increased metabolic processing of APP through the amyloidogenic pathway, further contributing to Aβ deposition, neuritic degeneration, and synapse loss in AD (Bignante, 2013) and DS.…”
mentioning
confidence: 99%